The influence of D-ribose ingestion and fitness level on performance and recovery - John G. Seifert; Allison Brumet; John A. St Cyr (Taylor & Francis Group, 2017)
Background Skeletal muscle adenosine triphosphate (ATP) levels are severely depleted during and following prolonged high intensity exercise. Recovery from these lower ATP levels can take days, which can affect performance on subsequent days of exercise. Untrained individuals often suffer the stress and consequences of acute, repeated bouts of exercise by not having the ability to perform or recovery sufficiently to exercise on subsequent days. Conversely, trained individuals may be able to recover more quickly due to their enhanced metabolic systems. D-Ribose (DR) has been shown to enhance the recovery in ATP; however, it is not known if recovery and performance can be benefitted with DR ingestion. Therefore, this study was designed to determine what influence DR might have on muscular performance, recovery, and metabolism during and following a multi-day exercise regimen. Methods The study was a double blind, crossover study in 26 healthy subjects compared 10 g/day of DR to 10 g/day of dextrose (DEX, control). All subjects completed 2 days of loading with either DR or DEX, followed by 3 additional days of supplementation and during these 3 days of supplementation, each subject underwent 60 min of high intensity interval exercise in separate daily sessions, which involved cycling (8 min of exercise at 60% and 2 min at 80% VO2max), followed by a 2 min power output (PO) test. Subjects were divided into two groups based on peak VO2 results, lower VO2 (LVO2) and higher peak VO2 (HVO2). Results Mean and peak PO increased significantly from day 1 to day 3 for the DR trial compared to DEX in the LVO2 group. Rate of perceived exertion (RPE) and creatine kinase (CK) were significantly lower for DR than DEX in the LVO2 group. No differences in PO, RPE, heart rate, CK, blood urea nitrogen, or glucose were found between either supplement for the HVO2 group. Conclusion DR supplementation in the lower VO2 max group resulted in maintenance in exercise performance, as well as lower levels of RPE and CK. Unlike no observed benefits with DEX supplementation.